2018
DOI: 10.1016/j.aquaculture.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Towards the standardization of brush border purification and intestinal alkaline phosphatase quantification in fish with notes on other digestive enzymes

Abstract: Assessing the activity of digestive enzymes is a common procedure in many biological, physiological and nutritional studies. After reviewing the available literature on fish digestive tract maturation and enzymatic activity (pancreatic and intestinal enzymes) published between 1994 and 2017, authors detected some possible methodological and/or interpretative inconsistencies in this kind of studies, and concluded that special attention should be paid on: i) the time of conservation of frozen samples prior their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 49 publications
(43 reference statements)
1
51
0
1
Order By: Relevance
“…Processed samples were analyzed within the first two months after their homogenization in order to prevent a loss of activity of the pancreatic and gastric digestive enzymes . The remaining homogenate was processed for intestinal brush border purification according to the recommendations of Gisbert et al (2018) in order to properly determine alkaline phosphatase, maltase and aminopeptdiase N activities. To initiate this process, the homogenate was centrifuged (9,000 g for 10 min at 4 °C), the precipitate discarded, then the supernatant centrifuged once again (34,000 g for 30 min at 4 °C).…”
Section: Enzymatic Assaysmentioning
confidence: 99%
“…Processed samples were analyzed within the first two months after their homogenization in order to prevent a loss of activity of the pancreatic and gastric digestive enzymes . The remaining homogenate was processed for intestinal brush border purification according to the recommendations of Gisbert et al (2018) in order to properly determine alkaline phosphatase, maltase and aminopeptdiase N activities. To initiate this process, the homogenate was centrifuged (9,000 g for 10 min at 4 °C), the precipitate discarded, then the supernatant centrifuged once again (34,000 g for 30 min at 4 °C).…”
Section: Enzymatic Assaysmentioning
confidence: 99%
“…For nonspecific immunity systems, both AKP and ACP were the marker enzymes of macrophage lysosomes in the organism and were also the important hydrolytic enzymes in nonspecific immunity (Gisbert et al. ; Xia and Wu ). They could kill invading pathogens and also accelerate the phagocytosis of phagocytes and the degradation rate of foreign bodies.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, the findings presented in Tables 3 and 4 indicated that the effluent with R. sphaeroides and biochemicals improved the nonspecific immunity and antioxidant capabilities by regulating the expression level of related genes. For nonspecific immunity systems, both AKP and ACP were the marker enzymes of macrophage lysosomes in the organism and were also the important hydrolytic enzymes in nonspecific immunity (Gisbert et al 2018;Xia and Wu 2018). They could kill invading pathogens and also accelerate the phagocytosis of phagocytes and the degradation rate of foreign bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Then, 1 ml of the supernatant was pipetted and stored at −20°C for assaying pancreatic (total alkaline proteases, trypsin, chymotrypsin, αamylase, bile salt activated lipase), gastric (pepsin) and intestinal cytosolic (leucine-alanine peptidase) enzymes. The rest of the homogenate was used for the purification of intestinal brush border membranes (Gisbert et al, 2018), which served to quantify the activity of alkaline phosphatase, aminopeptidase-N and maltase.…”
Section: Analysis Of Digestive Enzymesmentioning
confidence: 99%